Teachers’ Beliefs and Practices: The Implementation of TBLT in Indonesian Higher Education - Annisa Permata Islami; Fatiha Senom (STAI Hubbulwathan Duri, 2024)
Task-Based Language Teaching (TBLT) has emerged as a trend in numerous countries. TBLT provides a contextualized and student-oriented approach in the EFL classroom that enables students to develop language skills that are relevant to a variety of real-life contexts. However, there is limited research on TBLT beliefs among teachers in Indonesian higher education. This study explored at two English language teacher beliefs concerning the implementation of TBLT in higher education in Indonesia, as well as the contextual factors that impact their beliefs. Qualitative research using a narrative inquiry approach was used to provide descriptive data about the teachers' experiences in task-based language teaching (TBLT). Data were collected through semi-structured online interviews and analyzed using thematic analysis. Based on the data analysis, it emerged that teachers' beliefs are instrumental as they influence their teaching approaches and practices related to TBLT. Teachers who believe in the effectiveness of TBLT tend to be more active in implementing it in their teaching. The results also showed a gap between teachers' beliefs and knowledge about TBLT. In addition, contextual factors such as curriculum, social relationships between teachers and students, and institutional support also influence the successful implementation of TBLT in EFL classrooms.